Upaya Unit Pelayanan Disabilitas Kota Tangerang Selatan Dalam Pemenuhan Hak Pendidikan Anak Disabilitas Majemuk - Rizka Ayu Ramadanti; Muhammad Sahrul (International Forum of Researchers and Lecturers, 2024)
Children with multiple disabilities experience more complex limitations because they have two or more types of disabilities. This causes their rights to be neglected, including the right to education. Therefore, the Disability Service Unit of South Tangerang City is present in its role in fulfilling the educational rights of children with multiple disabilities so that child welfare can be realized. This research aims to find out the efforts of the South Tangerang City Disability Service Unit in fulfilling the educational rights of children with multiple disabilities. This research uses a qualitative approach with a descriptive method. Data were collected through interviews, observation, and documentation. Informants were selected by applying the purposive sampling technique. The results showed that the efforts of the South Tangerang City Disability Service Unit in fulfilling the rights of children with multiple disabilities are through providing social service programs in the field of non-formal education through pre-vocational skills. The activities that support it include eco-printing, soap making, cooking, and juice making.